Analisis Pendapatan Asli Daerah (PAD), Dana Alokasi Umum dan Belanja Modal terhadap Kinerja Keuangan Pemerintah Daerah Pada Kabupaten/Kota di Provinsi Sumatera Utara Tahun 2018-2020 - Winanda Chyntia Simamora; Gideon Setyo Budiwitjaksono (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of local revenue, general allocation funds, and capital expenditures on the financial performance of local governments. This research is a quantitative research. The sample used in this study uses purposive sampling, namely districts/cities in the provinc of North Sumatra that have had good financial performance at least 1 time based on the efficiency ratio (with a percentage of <100%) during 2018-2020. The results of the study indicate that there is an effect of regional original income and capital expenditure on the financial performance of local governments while general allocation funds have no effect on the financial performance of local governments.